MICRONODULAR ULTRASOUND LESIONS IN THE COLONIC SUBMUCOSA OF 42 DOGS AND 14 CATS. Issue 6 (27th June 2013) - Citi, Simonetta; Chimenti, Tommaso; Marchetti, Veronica; Millanta, Francesca; Mannucci, Tommaso
Abstract : Micronodular ultrasound lesions have been detected in the colonic submucosa of dogs and cats at our hospital. The lesions had rounded/oval shapes, measured 1–3 mm in size, and exhibited a hypo/anechoic ultrasonographic pattern. To our knowledge, these lesions have not been previously reported in human or veterinary patients. The purpose of this retrospective study was to determine whether micronodular lesions were associated with other abdominal ultrasound abnormalities or clinical findings. Medical records of dogs and cats with sonographic reports describing micronodular lesions within the colonic submucosa were reviewed. Concurrent ultrasonographic abnormalities were recorded and compared with clinical sidgns and follow‐up data. A total of 42 dogs and 14 cats met inclusion criteria. Concurrent sonographic abnormalities included the following: increased colon wall thickness (12.5%); small bowel wall thickening, altered layering, and/or hyperechoic mucosa (45%); abdominal effusion (29%); caudal mesenteric lymphadenopathy (46%); mesenteric lymphadenopathy (27%); and pericolic peritoneal fat reactivity (9%). Fifty of 56 animals presented with diarrhea. Twenty‐seven cases had clinical signs of colitis and ultrasonographic lesions were limited to the colonic submucosa. In nine cases, follow‐up examination at 6–8 weeks showed resolution of clinical and ultrasonographic signs. Ultrasonographic and clinical examinations in 17 patients at 12–18 months and in 20 patients at 18–30 months from initial diagnosis showed resolution of submucosal lesions and clinical signs of enteropathy. The authors propose that micronodular submucosal ultrasound lesions may represent reactive intraparietal lymphoid follicles and may be indicators of colonic inflammatory diseases in dogs and cats.